The effect of ethanol upon glucose homeostasis. - Dittmar, Elizabeth A. (University of Ottawa (Canada), 1977)
The effect of an intravenous infusion of ethanol upon the rates of glucose production (Ra) and overall glucose utilization (Rd) was examined in conscious dogs. The animal were studied in the postabsorptive state under basal conditions; during insulin-induced hypoglycaemia; in diabetes induced by pancreatectomy or after a four day fast. The rates of glucose production and utilization were calculated using 3H-labelled glucose as tracer. Changes in blood lactate, plasma glucose and radioimmunoreactive insulin concentrations were followed during the administration of ethanol. The estimated rate of ethanol utilization was determined in the four different states studied. The primed infusion of 0.24--0.29 mM/kg·min ethanol did not change the plasma glucose concentrations nor the rates of glucose production and utilization in normal or diabetic dogs in the postabsorptive state. A significant decrease in Ra prevailed for fifty-five minutes after the beginning of an ethanol infusion at the rate of 0.04 mM/kg·min to dogs fasted for four days. When the same dogs were again fasted for the same duration and administered ethanol at the rate of 0.25 mM/kg min, there was no significant changes in Ra. When insulin was infused at the rate of 4-7 mU/kg min in the presence of ethanol, ethanol had no effect upon the increase in Ra. during insulin-induced hypoglycaemia. During ethanol infusions to fasted of diabetic dogs, blood lactate concentrations increased and insulin levels did not change. In five of the six paired experiments in which hypoglycaemia was induced with insulin with or without ethanol, the plasma insulin concentrations were consistently higher in the presence of ethanol although the metabolic clearance rates of glucose remained unchanged. The estimated rates of ethanol utilization were reduced by fasting but not in diabetes or during insulin-induced hypoglycaemia. In conclusion, ethanol did not interfere with the elevated rate of gluconeogenesis in diabetes nor did it interfere with the hepatic response to hypoglycaemia.
Keywords: Biology, Animal Physiology.